Laryngeal tumours and radiotherapy dose to the cricopharyngeus are predictive of death from aspiration pneumonia. (January 2017) - O'Hare, Jolyne; Maclean, Julia; Szczesniak, Michal; Gupta, Rashmi; Wu, Peter; Quon, Harry; Cook, Ian; Graham, Peter
Highlights: Aspiration pneumonia is a leading cause of mortality following head and neck cancer radiotherapy. Risk factors that increase this mortality include laryngeal tumours and dose to cricopharyngeus. Increased clinical awareness of this potential high risk cohort is indicated. Abstract: Objectives: Aspiration pneumonia is an under-reported treatment sequelae following radiotherapy for head and neck cancer (HNC) patients. This study aims to investigate its incidence and risk factors in this population. Materials and methods: A retrospective review of all HNC patients that had received radiotherapy or chemo radiotherapy with radical intent at a single institution was undertaken (n = 206). Dose delivered to the pharyngeal constrictors, base of tongue and cricopharyngeus was calculated and compared between those patients who had died from aspiration pneumonia and those who are alive or had died from other causes. Results: In a cohort of 206 patients, the median time of follow up was 3.5 years (IQR 1.8–4.9 years). The cause of death was known in 80 and one of the leading causes of non-cancer related mortality was aspiration pneumonia (n = 12) equating to an annual incidence of 0.016. Patients with a tumour located in the larynx had a higher risk of death compared to other sites (p = 0.005). The mean cricopharyngeal dose was significantly higher in those patients who died of aspiration pneumonia (p = 0.023) compared to those who were still alive or had died from other causes. In a multivariate regression analysis, maximum cricopharyngeal dose is a significant predictor of death from aspiration pneumonia. Conclusion: Dose to the cricopharyngeus and tumours located within the larynx is associated with an increased mortality due to aspiration pneumonia. Clinical awareness of high risk groups and more studies into causative nature are needed.